2008
DOI: 10.1111/j.1747-6593.2007.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring, river restoration and the Water Framework Directive

Abstract: Monitoring is an important aspect of any procedure that seeks to determine whether a technique has worked effectively. The river restoration process is no different. Unfortunately, monitoring is often not undertaken due to constraints on time and resources, as well as the commonly held belief that river restoration is inherently a good thing and, as a result, monitoring is unnecessary. There are many reasons to monitor projects and among the most important is the need to learn from experiences and for regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…It is generally recognised that river hyporheic restoration requires a set of objectives against which the outcomes can be measured (England, Skinner & Carter, ) but this is often overlooked. This may in part be because there are very few guidelines to help support decision‐making processes in terms of the physical aspects of river restoration or the links between physical and chemical, hydrological or biological benefits.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognised that river hyporheic restoration requires a set of objectives against which the outcomes can be measured (England, Skinner & Carter, ) but this is often overlooked. This may in part be because there are very few guidelines to help support decision‐making processes in terms of the physical aspects of river restoration or the links between physical and chemical, hydrological or biological benefits.…”
Section: Discussionmentioning
confidence: 99%
“…, 2007), poor controls (reference systems; Boulton, 1999) and inadequate monitoring and assessment before and after restoration measures (Bernhardt et al. , 2005; England, Skinner & Carter, 2007). The importance of long‐term monitoring records has been demonstrated in the case of nitrate in rivers, where trends can be obscured by short‐term variability (Burt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is of paramount importance that resources should be targeted where they will produce the most beneficial impact on river restoration projects [30]. When discussing the frequently employed approaches to develop ecological restoration strategies, King and Hobbs concluded that "the structural approach tends to focus upon mechanical manipulations of components of ecosystem structure, whereas the functional approach instead attempts to manipulate the interactions and dynamics-the ecological processes-which have been degraded" [36].…”
Section: Necessity Of Moving Towards a Pressure-oriented Water Qualitmentioning
confidence: 99%
“…In the WFD, three types of monitoring (Annex V) are suggested: (i) surveillance monitoring-routine monitoring to aid in evaluating water status, designing future programmes, and assessing long-term changes due to natural and human activities; (ii) operational monitoring-target waters probably falling below their designed status usually in the short term, which may influence the direction of the programme of measures; and (iii) investigative monitoring-for waters at risk in problems areas with pollution incidence, which would lead to response measures [31]. In the domain of river restoration, most monitoring schemes are likely to be of use only for investigative monitoring [30].…”
Section: Dilemmas Of the Current Water Quality Monitoring Systemmentioning
confidence: 99%